Pharmacokinetics of Conventional and Long-Acting Oxytetracycline Preparations in Kilis Goat - Aktas, İbrahim; Yarsan, Ender (Frontiers in Veterinary Science, 2017)
The pharmacokinetics of conventional and long-acting oxytetracycline (OTC), widely used antibacterial drugs in veterinary medicine with a broad spectrum, were evaluated in Kilis goats at single dosage of 20 mg-kg-1 body weight (bw). A total of 21 goats were divided into three groups: Intravenous (IV) (Group I) and intramuscular (IM) (Group II) administration of the conventional formulation and IM administration of the long-acting formulation (Group III). Blood samples were taken at 0.25, 0.5, 1, 2, 4 8, 12, 24, 36, 48, 60, 72 and 96 hours; where OTC analysis was performed by HPLC. For Group III, and Group II, time to reach maximal plasma drug concentration (Tmax) were 0.6±0.28 and 0.46±0.09 hours and maximal plasma drug concentrations (Cmax) were 8.72±2.47 µg/ml, 13.57±5.83 µg/ml, respectively. In Group I, C0 concentration was found as 63.51±11.59 µg/ml. The elimination times (T1/2) were 10.84±3.20, 27.96±11.66 and 10.47±1.30 hours; and AUC were 115±29.12 µg/ml/h, 96.44±9.49 µg/ml/h and 80.86±12.76 µg/ml/h for Group I; Group II, and Group III respectively. Bioavailability by IM administration were 69.71% for the conventional OTC and 83.15% for the long-acting OTC.